The Management Of Foreign Exchange Reserves In Algeria - Ouaret, Samira; Yaici, Farid (جامعة الوادي - University of Eloued, 2020)
Foreign exchange reserves have long been a very important part of the international monetary system. These reserves have developed drastically, especially in recent years. In the second quarter of 2019, the amount of reserves in the world exceeded 11730 billion American Dollar. Today, the priority is not the accumulation of reserves, but their management policies. In Algeria, foreign exchange reserves have also grown significantly in recent years due to the rise in oil prices in the world market. Reserves reached a peak in 2013 with 194.012 billion Dollar. After the fall in oil prices in June 2014, reserves decreased to approximately 73 billion Dollar in the first quarter of 2019. Algeria has always chosen a prudent reserve management policy for the management of its reserves. In the 2000’s, various strategic measures were taken by Algeria, including the repayment of external debt and the creation of an Income Regulatory Fund. In this article, we will explain this management adopted by Algeria by examining the annual reports of the Bank of Algeria and analyzing the data collected from different sources: Bank of Algeria, the Ministry of Finance and others, using figures and then identify the shortcomings of this management policy.
مقال
Keywords: Foreign Exchange Reserves ; Algeria ; Reserve Management ; Revenue Regulation Fund ; Securities